Implementasi Kurikulum Merdeka pada Pembelajaran PKN Berbasis Study Case untuk Meningkatkan Civic Disposition pada Siswa Kelas VII di SMP Wahidiyah Karangrejo - Dwi Agustina Rahayu; Lusy Wahyu Saputri; Andreas Andrie Djatmiko (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The Merdeka Curriculum is a curriculum with intracurricular learning that is more optimized for varied learning content. Provide sufficient time for students to explore knowledge concepts and strengthen their competencies. Learning with the concept of independent learning prioritizes students' interests and talents, so that learning outcomes can foster creative attitudes and the learning process becomes more enjoyable. The formulation of the problem in this research is the role of the independent curriculum to increase civic disposition and its level of success as well as supporting and inhibiting factors for implementing the independent curriculum through Civics learning. The aim of this research is to determine the level of success of implementing the independent curriculum in improving civic disposition and what supporting and inhibiting factors exist. The research method used is a qualitative method with a qualitative descriptive approach. The instruments used are observation, interviews and documentation. The results of this research are that the implementation of the independent curriculum to improve the civic disposition of class VII students can be said to be quite good because it has implemented the independent curriculum in accordance with the curriculum objectives and succeeded in increasing students' understanding of character and moral values, as well as making a positive contribution to the formation of students' character. Although there are still some things that need to be improved, such as teaching materials to provide wider sources of information and using more varied learning strategies to increase students' active participation in Civics learning, especially for students who are still passive. Thus, the implementation of the Merdeka Curriculum at Wahidiyah Karangrejo Middle School has provided positive benefits in improving students' character and morals through Civics learning.